Analysis of the Insulation Quality of 1000 kVA Distribution Transformer Oil Due to Aging at PT. Bambang Djaja Surabaya - Reza Sarwo Widagdo; Puji Slamet; Aris Heri Andriawan; Bima Bayu Santoso (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
The reliability of transformer insulation is a crucial factor in preventing damage that can lead to fatal accidents and serious disruptions in electrical systems. Aging insulation can cause performance degradation in transformers, necessitating a comprehensive evaluation to detect potential damage at an early stage. This research aims to evaluate the condition of transformer insulation using several testing methods, namely Breakdown Voltage (BDV) and Dissolved Gas Analysis (DGA). Among these methods, DGA is the main focus due to its ability to detect internal disturbances early, such as heat release, arcing, and overheating. Dissolved gas analysis in insulating oil provides critical information to detect anomalies, allowing preventive measures to be taken before the damage becomes more severe. In this study, testing data from both BDV and DGA methods were obtained through experiments and observations on transformers that have been in operation for a certain period. The obtained data were thoroughly analyzed and compared with international standards, such as IEEE and IEC, to identify potential failures, such as insulation degradation, overheating, or abnormal energy release. The analysis results show that combining several testing methods, particularly DGA, can provide accurate results in detecting potential damage at an early stage. This research makes an important contribution to transformer management, especially in the implementation of predictive maintenance, to enhance the safety, reliability, and operational efficiency of transformers.